Estudo da compatibilidade de atemoia ((Annona cherimola Mill. X Annona squamosa L. CV. 'THOMOSON') enxertada em araticum-de-terra-fria [Annona emarginata (Schltdl.) H. Rainer variedade terra-fria] e biribá [[Annona mucosa (Bai.) H. Rainer] - Baron, Daniel [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Grafting is used efficiently for the commercial cultivation of fruit species, because it is necessary to ensure the genetic characteristics of productive species with the use of selected clones. Although grafting is common and widespread technique, mechanisms for compatibility in woody fruit are not well elucidated. Thus, the aim of this thesis was to study of restoring of atemoya (Annona cherimola Mill. x A.squamosa L. cv. 'Thompson') grafted onto atemoya (A. cherimola Mill. x Annona squamosa L. cv. 'Thompson'), araticum-mirim [A. emarginata (Schltdl.) H. Rainer 'variety mirim'], araticum-de-terra-fria [A. emarginata (Schltdl.) H. Rainer 'variety terra-fria'] and biribá [A. mucosa (Bail.) H. Rainer]. After grafting were evaluated gas exchange; plant growth; ionic concentration of mineral elements in the leaf and root tissues; determinations of the concentrations of phenolic compounds and peroxidase activity; UGP gene expression and enzymatic activity of UDP-glucose pyrophosphorylase (UGPase). Rootstocks modulate gas exchange by altering the carboxylation efficiency and transpiration, without, however showed favorable water economy. Changes in growth and concentrations of mineral elements in leaves and roots were also observed as a function of scion/rootstock combinations. In relation to the peroxidase activity, there was an increase in 'araticum-mirim' rootstock in relation to other species. Moreover, there were no differences in the concentrations of phenolic compounds in the grafted union, although these concentrations were higher than in rootstock. Grafting altered UGP gene expression, and the combination atemoya grafted onto 'araticum-de-terra-fria' (previously regarded as compatible combination) showed an increase in gene expression since the early stages after grafting. The results showed that there UGPase enzymatic activity, but there is no difference in this activity between different scion/ rootstock ...

A enxertia é utilizada de maneira eficaz para o cultivo de espécies frutíferas comercias, uma vez que é necessário garantir as caraterísticas genéticas de espécies produtivas com o emprego de clones selecionados. Apesar da enxertia ser técnica comum e amplamente difundida, os mecanismos de compatibilidade em frutíferas lenhosas ainda não estão bem elucidados. Desta forma, o objetivo desta tese foi estudar a restabelecimento da atemoieira (Annona cherimola Mill. x A. squamosa L. cv. 'Thompson') enxertada em atemoieira (A. cherimola Mill. x A. squamosa L. cv. 'Thompson'), araticum-mirim [A. emarginata (Schltdl.) H. Rainer variedade mirim, araticum-de-terra-fria [A. emarginata (Schltdl.) H. Rainer variedade terra-fria e biribá [A. mucosa (Bail.) H. Rainer]. Após a enxertia foram realizadas avaliações das trocas gasosas; de crescimento vegetal; análises da concentração iônica de elementos minerais no tecido foliar e radicular; determinações das concentrações de compostos fenólicos totais e atividade da peroxidase; expressão do gene UGP e atividade enzimática da UDP-glicose pirofosforilase. Os porta-enxertos modularam as trocas gasosas alterando a eficiência de carboxilação e a transpiração. Variações no crescimento e nas concentrações de elementos essenciais em folhas e raízes também foram observadas em função das combinações copa/porta-enxerto. Em relação a atividade da peroxidase, observou-se aumento no porta-enxerto araticum-mirim em relação às demais espécies. Por outro lado, não foram verificadas diferenças nas concentrações de compostos fenólicos nas regiões enxertadas, no entanto tais concentrações foram maiores do que nos péfrancos. A enxertia alterou a expressão do gene UGP, o que indica a possibilidade de maior formação de tecido de parede celular, sendo que a combinação atemoia enxertada ...
Study of compatibility of atemoya (Annona cherimola Mill. X Annona squamosa L. CV. 'THOMOSON') grafted onto araticum-mirim [Annona emarginata (Schltdl.)] H. Rainer Variedade mirim] araticum-de-terra-fria [Annona emarginata (Schltdl.) H. Rainer 'variedade terra fria' and biriba] e biriba [Annona emarginata (Schltdl.) H. Rainer]
Keywords: Anonacea; Biologia molecular; Enxertia; Plantas - Propagação; Peroxidase; Fenóis; Molecular biology; Plant propagation